Aplicação dos princípios de responsabilidade civil no direito antitruste - Magalhaes, Everton Claro (2024)
The present work aims to relate the application of civil liability in the field of antitrust law in relation to market illicit acts in order to seek civil reparation for the damages caused, as well as explore the current challenges for the application of the principles of civil liability in the antitrust sphere and propose viable improvements in light of the precepts of civil law and CADE's special regulation on the topic proposed herein